Relationships among cognition, emotion, and motivation: implications for intervention and neuroplasticity in psychopathology - Crocker, Laura D.; Heller, Wendy; Warren, Stacie L.; O'Hare, Aminda J.; Infantolino, Zachary P.; Miller, Gregory A. (Frontiers in Human Neuroscience, 2013)
Emotion-cognition and motivation-cognition relationships and related brain mechanisms are receiving increasing attention in the clinical research literature as a means of understanding diverse types of psychopathology and improving biological and psychological treatments. This paper reviews and integrates some of the growing evidence for cognitive biases and deficits in depression and anxiety, how these disruptions interact with emotional and motivational processes, and what brain mechanisms appear to be involved. This integration sets the stage for understanding the role of neuroplasticity in implementing change in cognitive, emotional, and motivational processes in psychopathology as a function of intervention.